DESCRIPTION OF SCIENCE PROCESS SKILLS OF SMAN 10 MUARO JAMBI’S STUDENTS ON THE EQUILIBRIUM MATERIAL ON THE ROPE - Febri Tia Aldila; Ricky Purnama Wirayuda; Mashelin Wulandari; Aziza Putri Ningsi (Universitas Negeri Medan, 2020)
Abstract. Physics is a subject that is related to other scientific concepts and can be applied in everyday life. So, the application of physics in learning really requires special skills, namely science process skills. Science process skills are divided into two, namely basic science process skills and integrated science process skills. This study aims to measure the ability of integrated science process skills of SMAN 10 Muaro Jambi students on the equilibrium material on the rope using observation sheets that are in accordance with the indicators of science process skills. This type of research is a descriptive study using a quantitative approach. The research design used was survey / observation research. This research was conducted in the physics laboratory of SMAN 1 Muaro Jambi in the academic year 2020/2021 with a sample of 40 students of SMAN 10 Muaro Jambi who majored in Mathematics and Natural Sciences (MIPA). The sampling technique used was purposive sampling technique. From the research results, it can be seen that the integrated science process skills of students at SMAN 10 Muaro Jambi are classified as good.